1998
DOI: 10.1007/bf03189334
|View full text |Cite
|
Sign up to set email alerts
|

Which bioequivalence study for a racemic drug? Application to milnacipran

Abstract: Milnacipran, a new non tricyclic antidepressant drug, is a racemic mixture (F2207) composed of two enantiomers: F2695 and F2696, both demonstrated to be active. A randomized open label, single-dose latin square study was undertaken in 24 healthy volunteers to compare, based on racemate data, the relative bioavailability of two new formulations to that of a reference formulation. Later on, as suggested by actual regulatory trend, analysis was carried out on enantiomer data, although in a supportive way. Bioequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…Parameters describing the pharmacokinetics of milnacipran in control subjects are in good agreement with previous observations made under similar conditions (3,8). As milnacipran is primarily eliminated via the renal route (Cl, / (CltoJF) = 0.5) with a strong active secretion process (CIR is 19.6 ± I.h-1 ) , it is not surprising that impaired renal function affects its pharmacokinetics.…”
Section: Discussionsupporting
confidence: 78%
“…Parameters describing the pharmacokinetics of milnacipran in control subjects are in good agreement with previous observations made under similar conditions (3,8). As milnacipran is primarily eliminated via the renal route (Cl, / (CltoJF) = 0.5) with a strong active secretion process (CIR is 19.6 ± I.h-1 ) , it is not surprising that impaired renal function affects its pharmacokinetics.…”
Section: Discussionsupporting
confidence: 78%
“…Examining the effects on functional outcomes in the fixed-dose study testing levomilnacipran 40, 80 and 120 mg/day (23), levomilnacipran 80 and 120 mg significantly improved SDS scores and the largest and most robust treatment effects were in the levomilnacipran 120 mg group. For functional remission, significant treatment advantage was found in patients with severe MDD (baseline MAD-RS score at least 35) who received the highest dosage of levomilnacipran (120 mg/day), with remission rates of 28% vs. 12%, resulting in a NNT of 7 (95% CI [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Short-term Trialsmentioning
confidence: 99%
“…Levomilnacipran is an active enantiomer of the racemic drug milnacipran (4,5); milnacipran itself is approved by the US FDA for the management of fibromyalgia (6) and in other countries for the treatment of MDD (7). MDD is a common disorder.…”
Section: Introductionmentioning
confidence: 99%
“…6), proving the specificity of the LC technique. It was further demonstrated that the major metabolic pathway of milnacipran in human went through glucuroconjugation [8,9]. Therefore, metabolites could not interfere with milnacipran because they were more polar and were early eluted.…”
Section: Discussionmentioning
confidence: 97%
“…The availability of a low cost bioanalytical method, easy to transfer and to set up, represents an advantage in therapeutic drug monitoring when required (control of compliance, overdose). The current method was used throughout the development of milnacipran and is, therefore, a pivotal reference when using pharmacokinetic data from major published trials [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%